Mecanismos para desarrollar e impulsar oportunidades de asosiaciones público privadas en el sector de acueducto y saneamiento básico a nivel nacional (2021)
The objective of this degree project is to research the PPP schemes applied to the aqueduct and sewerage sector in Colombia. These schemes have historically been implemented to solve infrastructure needs throughout the country. However in the aqueduct and sewerage sector they have not been able to be carried out successfully. Therefore, in this document, the current situation of the country is exposed in terms of this infrastructure, the reasons why it has not worked, cases of the country and other countries and finally recommendations, mechanisms, suggestions and studies to encourage PPP schemes in the aqueduct and basic sanitation sector